Navigating a corpus of journal papers using Handles - Chapman, Christopher; Brailsford, David F. (IOS Press, 2001)
For some years now the Internet and World Wide Web communities have envisaged moving to a next generation of Web technologies by promoting a globally unique, and persistent, identifier for identifying and locating many forms of published objects . These identifiers are called Universal Resource Names (URNs) and they hold out the prospect of being able to refer to an object by what it is (signified by its URN), rather than by where it is (the current URL technology). One early implementation of URN ideas is the Unicode-based Handle technology, developed at CNRI in Reston Virginia. The Digital Object Identifier (DOI) is a specific URN naming convention proposed just over 5 years ago and is now administered by the International DOI organisation, founded by a consortium of publishers and based in Washington DC. The DOI is being promoted for managing electronic content and for intellectual rights management of it, either using the published work itself, or, increasingly via metadata descriptors for the work in question.